Development of Civic Responsibility Competence in the Implementation of the Merdeka Curriculum - Ningrum, Putri Setiya; Muthali'in, Achmad (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
Curriculum development as an educational program has a solid foundation and principles to support implementing the expected national education goals. The decline in students' academic and character values, especially the low awareness of responsibility, is the urgency why this research was carried out. This study aims to determine the development of civic responsibility competencies in implementing the Merdeka Curriculum. This study uses a qualitative method with a descriptive design. Data collection techniques using interviews, observation, and documentation. It was then validated using triangulation to ensure the trustworthiness of the information obtained from the informants. Data analysis techniques in this study are data collection, reduction, presentation, and conclusion. The results of this study indicate that the development of civic responsibility competencies in implementing the Merdeka Curriculum in schools is very much needed. Developing an attitude of responsibility can be done through habituation, group work, and discussion. Developing civic responsibility competencies in implementing the Merdeka Curriculum is considered capable of equipping students to become good and responsible citizens. This research is expected to provide implications as reference material for further research.